CONSTRUCTION OF UML DIAGRAM IN DESIGNING PROGRAMS - Huliieva , Nataliia; Huliieva , Zemfira (Collection of scientific papers «ΛΌГOΣ», 2023)
When designing a software product, it is necessary to take into account its specificity and purpose, in this case, we will consider the construction of UML diagrams for a training program for children with autism spectrum disorders.